Protection and Distribution of Wealth, Islamic Commercial and Financial Transactions: A Maqasid Al-Shariah perspective - Khattak, Mudeer Ahmed (European Journal of Islamic Finance, 2018)
The purpose of this research is to discuss briefly about the Maqasid Al-Shari’ah, in the context of protection and distribution of wealth in society as well as its relevance in commercial and financial transactions in Islamic Finance and on society. The paper will cover specifically the major facet of Maqasid that are essential in the transactions and as well as the application of Maqasid in preservation and distribution of wealth for Islamic financial practices. Maqasid Al-Sharia’s role in consonance to Islamic financial services industry will also be discussed in brief to undermine the importance and to enlighten the relevance where Maqasid play a vital role in harmonizing Shari’ah rulings for the just and fair distribution of wealth in the society and to involve it under strategical behaviour of businesses, firms and banks, commercially and financially.